The Initial Findings on the Socioeconomic Impacts and Migration Patterns of the Marudi-Miri Tar-Sealed Road - Wong, Bemen Win Keong; Keelbisas , Mika Mus; Garai, Regina (GEOGRAFI, 2025)
The study investigates the socioeconomic impacts of the tar-sealed road connecting Marudi to Miri City in Sarawak, Malaysia. Before 2005, Marudi was disconnected from Miri City by road, depending solely on express boats and flights for its transportation needs. The construction of a logging road in 2005 and its subsequent upgrade to a tar-sealed road in 2019 significantly improved accessibility. This qualitative research utilises purposive sampling and employs semi-structured interviews with 20 interviewees to explore the impacts of the road. The findings reveal four primary social and economic impacts. The newly tar-sealed road has greatly enhanced patient transportation to hospitals and made travel more convenient. However, its narrow and hilly characteristics have raised safety concerns. In terms of migration, the primary factor influencing migration decisions continues to be economic opportunities. Economically, the road has altered consumer behaviour, leading to increased shopping in Miri and posing challenges for local businesses. However, it has also spurred new business developments, including national chain stores and local enterprises. The study finds that although the tar-sealed road has improved accessibility, it does not significantly influence the migration decisions of local residents. Instead, job opportunities continue to be the primary factor for migration.